BPM Methodology Applied in Construction Projects: A Reflection - Barrera-Alvarado, Julián-Gustavo; González-Sanabria, Juan-Sebastián; Sarmiento-Rojas, Jorge-Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The Business Process Management (BPM) methodology is emerging as an essential management philosophy in the optimization of business processes, demonstrating its relevance in the construction sector. In Colombia, where managing construction projects requires a more strategic approach, implementing BPM presents a valuable opportunity to improve efficiency and agility at all stages, from planning to after-sales. The effective integration of BPM represents a significant breakthrough, enabling companies to achieve higher levels of productivity and efficiency in a highly competitive environment. This article proves from the research the importance of the methodology and the potential benefit of its use in the different civil works projects since they are made up of processes. In the end, adopting the BPM methodology in the construction sector will not only optimize the management of projects but will also contribute to the sustainable growth and global development of this fundamental industry.